2016
DOI: 10.3389/fncel.2016.00035
|View full text |Cite
|
Sign up to set email alerts
|

How Necessary is the Vasculature in the Life of Neural Stem and Progenitor Cells? Evidence from Evolution, Development and the Adult Nervous System

Abstract: Augmenting evidence suggests that such is the functional dependance of neural stem cells (NSCs) on the vasculature that they normally reside in “perivascular niches”. Two examples are the “neurovascular” and the “oligovascular” niches of the adult brain, which comprise specialized microenvironments where NSCs or oligodendrocyte progenitor cells survive and remain mitotically active in close proximity to blood vessels (BVs). The often observed co-ordination of angiogenesis and neurogenesis led to these processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Mammalian adult neurogenesis occurs at two specific sites, the subventricular zone lining the lateral ventricles and the subgranular zone of the hippocampal dentate gyrus. These neurogenic sites are equipped with both germinal layer‐derived NSCs and highly structured neurogenic niches (Bonfanti & Peretto, ; Kempermann, ; Koutsakis & Kazanis, ; Lindsey & Tropepe, ; Ming & Song, ). On the other hand, adult neurogenesis in locations that are putatively nonneurogenic remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian adult neurogenesis occurs at two specific sites, the subventricular zone lining the lateral ventricles and the subgranular zone of the hippocampal dentate gyrus. These neurogenic sites are equipped with both germinal layer‐derived NSCs and highly structured neurogenic niches (Bonfanti & Peretto, ; Kempermann, ; Koutsakis & Kazanis, ; Lindsey & Tropepe, ; Ming & Song, ). On the other hand, adult neurogenesis in locations that are putatively nonneurogenic remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial BDNF also attracts neuroblasts and netrin-1 is required for oligodendroglial progenitor migration to the corpus callosum (Figure 3). 100 Conditioned media from vascular cell cultures promote neuronal differentiation, as does the basic helix-loop-helix proneural transcription factor Neurod1. Post-stroke angiogenesis has been observed in patients 101,102 and mechanisms similar to how axonal growth cones explore their surroundings have been described with tip cells sensing guidance cues.…”
Section: Structural Remodeling In Strokementioning
confidence: 99%
“…Then, Tsai et al reported that physical interactions with ECs are required for OPC migration and differentiation [25]. Afterwards, several studies demonstrated that destruction of oligovascular niche triggered CNS inflammation, blocked oligodendroglial differentiation, caused cerebral small vessel disease vulnerability, and aggravated white matter damage [26][27][28][29]. Here, we reported conditioned media from OGD-ECs caused OPC apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 58%